Enantioselective synthesis of cyclic α-aminoboronates via copper-catalyzed dearomative borylation of 4-quinolinols. Issue 22 (28th February 2022) - Xu, Ming; Ouyang, Yizhao; Wang, Linghua; Zhang, Shuai; Li, Pengfei
Abstract : An enantioselective and regioselective dearomative borylation of 4-quinolinols was developed for synthesis of unprecedented heterocyclic α-amino boronates, a new class of compounds potentially relevant to drug discovery. Abstract : A highly enantioselective and regioselective dearomative borylation of 4-quinolinols was developed using a Cu(i )/( R, R )-Ph-BPE catalyst for efficient synthesis of unprecedented heterocyclic α-amino boronates, a new class of compounds potentially relevant to drug discovery, in generally excellent yields and enantioselectivities. The products were also useful intermediates for highly functionalized tetrahydroquinolines and cyclic α-aminoboronate derivatives.